Técnicas de preferência declarada: uma aplicação no setor hoteleiro de Bagé/RS - (:unkn) unknown (Universidade Federal do Pampa, 2016)
There is a growing concern for companies to understand how individuals perform their consumer choices. More and more are being conducted studies that seek to estimate consumer preferences. A technique widely used and consagrated in literature is the stated preference. For sectors such as hospitality, this tool has great value in this segment because of the difficulty existing in the determination of the most relevant services in the opinion of the guests. This difficulty is due to the fact of the rating given to the hotel services are very subjective and difficult to measure. Since the importance of studying consumer preferences of hotel services, this study will use the stated preference technique to investigate the preferences of the guests of hotels in the city of Bagé/RS. The motivation of this work is based on the lack of studies of consumer preferences from the city hotels, especially in the new reality that Bage is experimenting with the arrival of major investments in the region.
Keywords: Engenharia; Engenharia de produção; Setor hoteleiro; Preferência declarada; Teoria do consumidor; Bagé; CNPQ::ENGENHARIAS